The impacts of type and proportion of five different asphalt modifiers on the low temperature fracture toughness and fracture energy of modified HMA (Fracture and Structural Integrity, 2018)
Low temperature fracture toughness and fracture energy are two important measures that could be used to investigate the impacts of using asphalt modifiers on the performance of asphalt pavements in cold regions. The aim of this research was to identify the impacts of using various proportions of five different asphalt modifiers on the fracture toughness and the fracture energy of Hot Mix Asphalts (HMA) under mode I loading and at low environmental temperatures. The asphalt modifiers used for this purpose were: Elastoplastomer Polymer Strings (EPS), Parafiber, Sulfur Polymer, Polyolefin-Aramid Compound Structural Fibers (PACSF) and Sasobit. These modifiers were individually used at three different proportions to produce Semi-circular Bend Specimens containing vertical edge crack. Each specimen was then tested under symmetric monotonic three-point bend loading at -15°C. The results indicated that, except for the EPS, both measures were increased with an increase in the modifier proportion. The most increase in the both measures was observed in the specimens modified with the PACSF, closely followed by specimens modified with the Parafibers. The least increase in these two measures were observed in the specimens modified with the Sulfur Polymer. The results indicated the applicability of examined modifiers to improve the resistance of HMA to crack initiation and crack growth at low temperatures.
Keywords: Mode-I Fracture Toughness; Mode-I Fracture Energy; Hot Mix Asphalt; Low-Temperature Cracking; Asphalt Modifiers